From Global Savings Glut to Financing Infrastructure : The Advent of Investment Platforms - Arezki, Rabah (IMF Working Papers; Working Paper ;, 2016)
This paper investigates the emerging global landscape for public-private co-investments in infrastructure. The creation of the Asian Infrastructure Investment Bank and other so-called 'infrastructure investment platforms' are an attempt to tap into the pool of both public and private long-term savings in order to channel the latter into much needed infrastructure projects. This paper puts these new initiatives into perspective by critically reviewing the literature and experience with public private partnerships in infrastructure. It concludes by identifying the main challenges policy makers and other actors will need to confront going forward and to turn infrastructure into an asset class of its own.